No sex difference was found in the safety and efficacy of intravenous alteplase before endovascular therapy - Fang, Min; Xu, Chenhaoyi; Ma, Lan; Sun, Yue; Zhou, Xiaoyu; Deng, Jiangshan; Liu, Xueyuan (Frontiers in Neurology, 2022)
Background and Purpose: Prior studies on sex disparities were post hoc analyses, involved limited treatment modalities and had controversial findings. Our study aimed to examine whether sex difference modifies the effect of intravenous alteplase before endovascular therapy. Method：We conducted a multicentered prospective cohort study of 850 eligible patients with acute ischemic stroke underwent endovascular therapy. Propensity score was utilized as a covariate to achieve approximate randomization of alteplase pretreatment. Baseline characteristics were compared between females and males. Logistic regression with interaction terms, adjusted for potential cofounders, was used to investigate the effect of sex on the prognosis of bridging therapy. Results: Females were older (78.00[70.00-84.00] vs 67[61.00-74.00], P<0.001), suffered more from atrial fibrillation (61.4% vs 35.2%, P<0.001), had a lower ASPECTS (10.00[8.00-10.00] vs 10[9.00-10.00], P=0.0047), a higher NIHSS score (17.00[14.00-20.00] vs 16[13.00-19.00], P=0.005) on admission than males. Female tended to receive less bridging therapy (26.3% vs 33%, P=0.043) and more retrieval attempts (2.00[1.00-2.00] vs 1[1.00-2.00], P=0.026). There was no sex difference on the functional independence 90 days after bridging therapy (OR 0.968, 95% CI 0.575–1.63), whereas males benefited more after endovascular therapy alone (OR 0.654, 95% CI 0.456–0.937). No sex-treatment interactions were observed regardless of the location of occlusion. Sex differences in all safety outcomes were not significant. Conclusion:Our study could not confirm sex modifies the treatment effect of intravenous alteplase before endovascular therapy. In the same time, we advocate for female to seek timely medical treatment.